Fomes weberianus, 50 years of taxonomic confusion: lectotypification and taxonomic notes - Cony Decock; Milay Cabarroi-Hernández; Laura Guzmán-Dávalos; Paul M. Kirk; José Ángel García-Beltrán; Mario Amalfi (IMA Fungus)
Abstract Fomes weberianus Bres. & Henn. ex Sacc. is currently the basionym of two very distinct polypores (Basidiomycota), Ganoderma weberianum (Polyporales) and Phylloporia weberiana (Hymenochaetales). This fact has led to almost fifty years of taxonomic confusion. Fomes weberianus was first lectotypified by Steyaert, who accepted the species as G. weberianum. However, studies of Weber’s original material in B, duplicate material in S, the protologue, and early interpretations of the name have shown that Steyaert’s choice conflicts with the protologue and early interpretations, and that his interpretation as a species of Ganoderma is erroneous. A new lectotype was designated and the species was re-described under the correct interpretation Phylloporia weberiana.